Pembuatan Indeks Beranotasi Surat Kabar tentang Pariwisata Pesisir Selatan Koleksi Perpustakaan Dinas Kearsipan dan Perpustakaan Kabupaten Pesisir Selatan - Melia Hanum; Malta Nelisa (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
This paper discusses about the making of an annotated index of the newspaper about Pesisir Selatan tourism collection of the Library Archives and Library Department of Pesisir Selatan Regency. The purpose of this paper are (1)to see how the condition of newspaper collections in the Office of Archives and the Library of the South Coast (2) to describe the proces of making an annotated index of newspapers on tourism in the Archives and Library Department in the Pesisir Selatan. The Making of newspaper indexes in 2016-2017 in the Archives and Library Department in Pesisir Selatan was done by collecting data directly from the original source, ie newspapers in the Archives and Library Department in the Pesisir Selatan. The type of research was making of an annotated index of newspapers about Pesisir Selatan tourism collection of Library of Archives and Library Department of Pesisir Selatan Regency which conducted in this paper by using descriptive method that was done by collecting data directly from the original source, namely newspapers in the Office of Archives and Library of Pesisir Selatan Regency . Based on data analysis, it concluded that (1) In a effort to optimize and utilize libraries in finding information, an information-seeking tool was required to index newspaper-annotated articles that describe the entire information contained in newspaper articles; (2) index as inormation seaching tool, especially for newspapers in the office of archives and library department in the Pesisir Selatan was expected to help the user in finding the information needed accurately and quickly.Keyword: annotated index, newspaper, tourism.